Review of Anti-Diabetic Properties of Moringa oleifera (Drumstick) and Psidium guajava (Guava) Leaves (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycaemia arising from impaired insulin secretion, insulin resistance, or both, affecting over 382 million people worldwide with projections nearing 592 million by 2035. Conventional antidiabetic therapies, while effective, are often associated with adverse effects, high cost, and limited accessibility, prompting growing interest in safer, plant-derived alternatives. This review evaluates the anti-diabetic potential of Moringa oleifera (drumstick) and Psidium guajava (guava) leaves through a comprehensive analysis of existing in-vitro, in-vivo, and clinical literature. Both plants are rich in bioactive phytoconstituents—flavonoids, phenolic acids, alkaloids, tannins, and saponins—that exert hypoglycaemic effects through complementary mechanisms, including inhibition of the carbohydrate-digesting enzymes α-amylase and α-glucosidase, enhancement of insulin secretion and sensitivity, reduction of hepatic glucose production, and protection of pancreatic β-cells from oxidative damage. Drumstick leaf extracts demonstrated strong α-amylase inhibition (95–99%) and antioxidant activity (up to 81% DPPH scavenging), while isolated guava-leaf compounds such as ellagic acid and quercetin showed α-glucosidase inhibition (IC₅₀ 25–72 μg/mL) comparable to or exceeding the standard drug acarbose. Clinical and animal studies further support reductions in fasting and post-prandial blood glucose, improved lipid profiles, and favourable safety outcomes. Collectively, the evidence positions drumstick, and guava leaves as promising, low-cost, complementary therapies for Type 2 diabetes management. However, most findings remain pre-clinical, underscoring the need for standardized dosing protocols and large-scale human trials to validate their therapeutic application alongside conventional antidiabetic regimens.
Keywords: Diabetes mellitus; Moringa oleifera; Pisidium guajava; antidiabetic activity phytochemicals; alpha amylase; alpha glucosidase inhibition; Antioxidants